(untitled) (Lapai Journal of Economics, 2021)
This study analyzes the nexus between telecommunication infrastructure investment and economic growth in Nigeria using time series data for the period of thirty-nine (39) years (1981-2019). In analyzing the data, the study used Autoregressive Distributed Lag (ARDL) approach and Granger Causality Test. The results reveal that telecommunication investment and telecommunication revenue exert a positive impact on economic growth in both long run and short run. The Granger causality analysis divulges the existence of a bidirectional causality between telecommunication investment and GDP, telecommunication revenue and GDP as well as telecommunication revenue and telecommunication investment. Furthermore, there is no causality between teledensity and the other variables; GDP, telecommunication investment and telecommunication revenue. The study therefore, recommends that government should give more licenses to GSM operators, provide concessionary fiscal incentives and aggressively promote investment in fixed telecommunication assets.